Community-Based Monitoring of Jaguar (Panthera onca) in the Chinantla Region, Mexico. (April 2020) - Lavariega, Mario C.; Ríos-Solís, Jesús Alejandro; Flores-Martínez, José Juan; Galindo-Aguilar, Rosa Elena; Sánchez-Cordero, Víctor; Juan-Albino, Silvano; Soriano-Martínez, Ixchel
Successful community-based wildlife monitoring necessitates a high degree of local participation during sampling design and data collection. Here, we describe a community-based monitoring framework to estimate density and habitat use of the threatened jaguar ( Panthera onca ) in tropical montane forests in the Chinantla region of Oaxaca, Mexico. Community-based monitoring was completed involving integration with local communities, local governmental agencies, nongovernmental organizations, and academic institutions. In a camera-trap survey (37 stations, 2, 553 trap-days), we recorded eight adult jaguars across 182.7 km 2 of montane forest. Spatially explicit capture–recapture models estimated a density of 1.15 jaguars per 100 km 2 (CI = 0.55–2.38) using a more traditional likelihood-based method and 1.16 jaguars per 100 km 2 (CI = 0.89–1.57) using Bayesian methods. The locations of jaguar captures and their habitat use appeared to be influenced by normalized vegetation index and capture rate of prey. Density estimates in the Chinantla region were lower than recorded for other lowland populations in Mexico but were consistent with elevation-based and latitudinal gradients across the range of the species. The community-based monitoring of jaguars increased the communication and interaction of local community groups, stakeholders, and academic institutions. It also provided participants with an increased knowledge of wildlife identification, transferable skills, wildlife appreciation, and an interest in reaching compromises to achieve habitat conservation. Our study provides a framework for the execution of community-based monitoring for large carnivores in Mexico and can be readily replicated and applied to other threatened species.